Promoting Qarḍ al-Ḥasan in Nanofinance to Counter The Moneylender in Southeast Asia - Khairunnisa Musari (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2019)
Moneylending is a real humanitarian problem in Asian countries, including in Southeast Asia. This study examines moneylending activities in this region, where poor people become a target. An emergency need forces them to seek out a moneylender. This paper argues that nanofinance may address the microfinance gap to counter the moneylender. Despite the existence of nanofinance, it has not obtained as much attention as microfinance. However, nanofinance activities have run in some Asian countries to help the poor. By interviewing some informants in Indonesia, Vietnam, and Cambodia, and then reviewing the empirical study and context in Malaysia, Thailand and Brunei, this paper intends to: (1) Describe the practice of moneylending in Indonesia, Vietnam, Cambodia, Malaysia, Thailand and Brunei; (2) Describe the nanofinance practice in Indonesia and Thailand; (3) Promote qarḍ al-ḥasan as the philanthropy contract of (Islamic) nanofinance.